INNOVATION CAPABILITY AND MARKET ORIENTATION RESEARCH MODEL ON BUSINESS PERFORMANCE OF CHICKEN NOODLE UMKM IN BEKASI - Syahyono, Syahyono; Oktavia, Ayu; Rohanah, Rohanah; Febriyanti, Elfiana; Adawiyah, Robiatul (Jurnal Bina Bangsa Ekonomika, 2025)
Innovation and market orientation have now become important components for the sustainability and competitiveness of small businesses, especially MSMEs (Micro, Small, and Medium Enterprises) in Indonesia, due to the rapid growth of the culinary industry. Analyzing the impact of market orientation and innovation capability on the business performance of Mie Ayam SMEs in Bekasi City is the objective of this research. A quantitative correlational approach is used in this research. A sample of 100 Mie Ayam SME owners was selected through purposive sampling based on predetermined criteria, such as a minimum operational period of two years and consistent monthly income. The population of this study is MSMEs in the culinary industry. Surveys using structured questionnaires were employed to collect data, and the Partial Least Squares (PLS) approach was utilized for analysis. This research reveals that innovation capability significantly enhances business performance by driving improvements in products, processes, and strategies in line with market demand. Similarly, market orientation contributes positively by enabling businesses to understand consumer needs and respond to competitive dynamics. The synergy between these variables strengthens their impact, allowing SMEs to maintain relevance in a highly dynamic market. This study highlights the importance of integrating innovation and market orientation as strategic tools to sustain growth and enhance competitiveness. These results offer practical insights for MSME owners and policymakers to develop strategies that support the resilience and development of the culinary industry in the local context